Innate immunity as a target for acute cardioprotection - Zuurbier, Coert J; Abbate, Antonio; Cabrera-Fuentes, Hector A; Cohen, Michael V; Collino, Massimo; De Kleijn, Dominique P V; Downey, James M; Pagliaro, Pasquale; Preissner, Klaus T; Takahashi, Masafumi; Davidson, Sean M (Cardiovascular research, 2019)
Acute obstruction of a coronary artery causes myocardial ischaemia and if prolonged, may result in an ST-segment elevation myocardial infarction (STEMI). First-line treatment involves rapid reperfusion. However, a highly dynamic and co-ordinated inflammatory response is rapidly mounted to repair and remove the injured cells which, paradoxically, can further exacerbate myocardial injury. Furthermore, although cardiac remodelling may initially preserve some function to the heart, it can lead over time to adverse remodelling and eventually heart failure. Since the size of the infarct corresponds to the subsequent risk of developing heart failure, it is important to find ways to limit initial infarct development. In this review, we focus on the role of the innate immune system in the acute response to ischaemia-reperfusion (IR) and specifically its contribution to cell death and myocardial infarction. Numerous danger-associated molecular patterns are released from dying cells in the myocardium, which can stimulate pattern recognition receptors including toll like receptors and NOD-like receptors (NLRs) in resident cardiac and immune cells. Activation of the NLRP3 inflammasome, caspase 1, and pyroptosis may ensue, particularly when the myocardium has been previously aggravated by the presence of comorbidities. Evidence will be discussed that suggests agents targeting innate immunity may be a promising means of protecting the hearts of STEMI patients against acute IR injury. However, the dosing and timing of such agents should be carefully determined because innate immunity pathways may also be involved in cardioprotection. This article is part of a Cardiovascular Research Spotlight Issue entitled 'Cardioprotection Beyond the Cardiomyocyte', and emerged as part of the discussions of the European Union (EU)-CARDIOPROTECTION Cooperation in Science and Technology (COST) Action, CA16225.